2017
DOI: 10.22159/ajpcr.2017.v10i10.19450
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Anticancer and Anti-Lipoxygenase Activities of Chia Seed Oil and Its Blends With Selected Vegetable Oils

Abstract: Objective: To investigate the anticancer and anti-inflammatory potential of chia seed oil (CSO) and its blends in vitro. Methods:The in vitro cancer cytotoxic properties ability of CSO and its blends was evaluated by (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) (MTT) and trypan blue assays using major cell lines including chronic myelogenous leukemia, HeLa and MCF-7 cells. The anti-inflammatory effect of the CSO and its blends was studied by assessing the anti-lipoxygenase (LOX) activity in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Numerous findings have confirmed that chia seed oil is a healthy oil for lowering the risk for cardiovascular disease, hepatoprotective effect, inflammation, and prevention of obesity-related disorders [6]. At present, the in vitro cancer cytotoxic properties of CSO have been reported by Ramzi et al, who showed that the CSO significantly inhibited the proliferation of human lymphoblastic leukemic cell lines, HeLa, and MCF-7 cells [7]. Up to now, there has been no evidence of adverse effects of chia seeds, and toxicological data on CSO from animal and controlled human trials on the safety and efficacy are still limited.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous findings have confirmed that chia seed oil is a healthy oil for lowering the risk for cardiovascular disease, hepatoprotective effect, inflammation, and prevention of obesity-related disorders [6]. At present, the in vitro cancer cytotoxic properties of CSO have been reported by Ramzi et al, who showed that the CSO significantly inhibited the proliferation of human lymphoblastic leukemic cell lines, HeLa, and MCF-7 cells [7]. Up to now, there has been no evidence of adverse effects of chia seeds, and toxicological data on CSO from animal and controlled human trials on the safety and efficacy are still limited.…”
Section: Introductionmentioning
confidence: 99%
“…Being rich in PUFAs, CSO showed inhibitory activities against tumors or uncontrolled cell growth and therefore could potentially be considered as a good therapeutic source in the treatment of cancer. CSO and its blends with soybean and palmolein showed in vitro cytotoxic properties against cancerous cells lines (chronic myelogenous leukemia, HeLa, and MCF‐7) by MTT and Trypan blue assays (Gazem et al., 2017). Administration of 400 µg/ml of CSO to tumor cells, breast cancer cell line MCF‐7, showed enhanced cell viability (159.8 ± 4.5%), which was determined by the (3‐(4,5‐dimethyl thiazole‐2yl)–2,5‐diphenyl tetrazolium bromide) MTT assay.…”
Section: Cso Applicationsmentioning
confidence: 99%
“…Chia seeds contain fat (30 to 33%) and proteins (15 to 25%) (Ixtaina et al, 2008). More than 60% of its fat contains polyunsaturated fatty acids (PUFA), mainly Omega 3 and 6 fatty acids (Di Marco et al, 2020;Ghafoor et al, 2020;Grancieri et al, 2019;Rajaram, 2014;Segura-Campos et al, 2014;Shen et al, 2018) are vital to human health throughout one's lifespan (Gazem et al, 2017;Wu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%